Os jovens e o ensino médio: a mobilização dos sujeitos para o saber em contextos escolares - Amaral, Juciara Saviana Machado do (2016)
This study aims to understand elements that permeate the intellectual mobilization of high school students towards learning in school settings. The central question that drives this research is justified by different studies and data sources that have shown that high school is the education level where we can find the highest number of school dropouts, failures and age/grade delay. These problems are also frequently related to quality issues. In order to identify elements that characterize the intellectual mobilization of high school students three methodological tools of qualitative nature were used: socioeconomic questionnaire, semistructured individual interviews and focus group. The participants of the study are eight students from a philanthropic private school located within Rio Grande do Sul state. The theoretical framework underlying the analysis of data produced is embodied in the studies by Bernard Charlot (2000, 2001 and 2005) and Jean Piaget (2014), and the work of other researchers such as John Dewey (1978), Edouard Claparéde (1940) and Bransford, Brown and Cocking (2000). For the understanding of the young who enter this school stage, we dialogue with Álvaro Marchesi (2006), Juarez Dayrell (2003 and 2014), Marilia Pontes Sposito (2004), among others. The results point to some key elements that can be observed when intellectual mobilization occurs: family presence, influence of school environment, recognition of the school as an important source of knowledge and cognitive practices, the prevalence of will and interest in studying as well as the young’s future projects. From these elements, it is proposed a deeper look on these recurring elements that are not frequently explored by postgraduation studies.